MARGINAL ADAPTATION OF SELF ADHESIVE (SUREFIL ONE) AND CONVENTIONAL BULKFILL COMPOSITES: AN-IN VITRO STUDY - IBRAHIM , MARYAM FAKHER; SELIVANY, BAHAR JAAFAR (Journal of Duhok University, 2023)
Purpose: To evaluate adaptability of self-adhesive Surefil one and two conventional bulkfill composites Beautifil bulk restorative and Filtek one bulk fill restorative. Materials and Methods: A total of sixty non carious extracted human premolars were selected for this study. Standardized proximal class ll cavity preparations were prepared on distal side and the samples were divided randomly into 3 equal groups (n=20) according to composite used, GI: Beautifil bulk restorative, GII: Filtek One Bulk fill restorative, GIII: Surefil one self-adhesive. All samples were exposed to thermal cycles and were sectioned longitudinally, then were sheltered with gold spray and analyzed on Scanning electron microscope for assessment of marginal adaptation. Results: Filtek one bulkfill restorative showed excellent adaptation with the walls of the cavity followed by Beautifil bulk and Surefil one self-adhesive. Furthermore, gingival margin showed the highest spaceamong other margins. Conclusion: Beautifil bulk and One bulk fill performed better results regarding marginal adaptation in all thirds of the cavity of class II cavity. Surefil one showed inferior results than others